Reflections on Photos of Political Power and Public Perception of the Joko Widodo-K.H. Ma'ruf Amin and Prabowo Subianto-Sandiaga Uno Victory Declaration Photos - Senaharjanta, Ignasius Liliek; Ronda, Andi Mirza; Dua, Mikhael (Future Science, 2023)
Photography can be used as a means to convey a narrative or a message behind the presented visuals. In the context of political communication, narrative has the power to influence and win opinions. In regard to this, one particular political narrative at which it is interesting to take a closer look among the political moments in Indonesia is the victory declaration in the 2019 Presidential Election contest. Victory declaration is a political phenomenon that occurred in the 2014 and 2019 Presidential Elections. In both occasions this event led to riots. Based on the description above, the research questions are: (1) How is visual photography produced as a medium to convey narratives within political message? and (2) How does the public as viewers or recipients of political messages perceive political messages in the visual form? This study aimed to identify the meaning of political narratives and the interrelationships of photography in the political context in Indonesia. The method employed in this study was Paul Ricœur’s Hermeneutics, with reference to semantic understanding, reflective understanding and existential understanding. An interpretive paradigm with data sources in the form of declaration photos, interviews with photographers and viewers. Our results showed that political success depends on individual aspects in carrying out their roles. In this context these roles of the individuals refer to political figures, agents and supporters. Interrelationships between roles in such group of individuals mainly revolve around cooperation in realizing common prosperity in political goals. This study concludes that cooperation between politicians, agents and supporters must be guided by political ethics as the main guideline for behaving and acting for the sake of achieving common prosperity. In addition, the use of technology in politics must be guided by ethics as an effort to realize a political system that is just, responsible, trustworthy, and meets the moral standards expected by society. Together, individuals, including politicians, agents and society, broadly play the role of moral agents to achieve politics with integrity, honesty and trustworthiness.